Leading Digital Transformation in MSMEs: A Qualitative Study of Leadership and Innovation in Banten, Indonesia - Sutardi, Didi; Johan, Muhammad; Asbari, Masduki; Wiyono, Nuri (IJOSMAS, 2026)
Digital transformation has become a critical imperative for micro, small, and medium enterprises (MSMEs) in responding to rapidly changing market dynamics and technological disruptions. While prior studies have largely emphasized technological adoption, limited attention has been given to the leadership processes that shape digital transformation and innovation within MSMEs, particularly in emerging economies. This study aims to explore how leadership drives digital transformation and innovation among MSMEs in Banten Province, Indonesia. Adopting a qualitative and interpretive research design, the study draws on in-depth interviews with 15 MSME owners and senior managers across diverse sectors, complemented by thematic analysis of their lived experiences. The findings reveal that digital transformation in MSMEs is fundamentally a leadership-driven process, rooted in leaders’ mindsets, sense-making, and strategic interpretations of digital technologies. Leaders who perceive digitalization as a long-term strategic opportunity tend to adopt proactive, integrative approaches that foster incremental innovation in marketing, operations, and customer engagement. Conversely, reactive leadership orientations result in fragmented and superficial digital adoption. The study further identifies hands-on leadership, employee empowerment, and resource mobilization as key practices enabling digital adoption and innovation despite significant resource constraints. Contextual factors such as limited digital skills, financial uncertainty, and regulatory complexity shape transformation trajectories; however, leadership agency plays a decisive mediating role in navigating these challenges. This research contributes to the digital transformation and leadership literature by highlighting the centrality of leadership in shaping innovation outcomes within MSMEs and offers practical insights for policymakers and development institutions seeking to strengthen leadership capacity as a foundation for inclusive and sustainable digital transformation.